Muscle mechanics during human movement revealed by in vivo measurements of tendon force and muscle length - Finni, T. (Studies in Sport, Physical Education and Health, 2001)
The present series of experiments utilized in vivo tendon force and fascicle length measurements for studying muscle mechanics during human locomotion. The behavior of quadriceps femoris and triceps surae muscle groups was examined in several different jumping exercises as well as during isokinetic knee and ankle extensions. In order to know how the muscle functions in natural locomotion as compared to its output during maximal constant velocity conditions, interaction between muscle and tendon lengths was studied. Special emphasis was given for understanding the benefits of prestretch in stretch-shortening cycle (SSC) of muscle function. The results suggest that there may be several interactive, task specific mechanisms that contribute to the enhanced performance in SSC exercises. Together with external loading conditions, the varying neural activity pattern sets the conditions for elastic energy storage and recoil by controlling the relative changes in muscle and tendon lengths. Greater activity level and force in a drop jump, for example, emphasize the role of elastic recoil from tendons as compared to a counter movement jump where also other mechanisms need to be acknowledged. Results from both submaximal jumps and maximal knee extensions suggest that enhancement may be related to length dependent behavior of muscle force. In addition to these mechanisms, contractile potentiation can have a role in SSC but may not be responsible for the major enhancement occurring in late concentric phase at high shortening velocities. Results from hopping with small knee-joint angular displacement suggest that there may be a particular frequency and jumping height at which the elastic bouncing is best utilized and at the same time the concentric phase is most economical. Results also support earlier observations that the economy of the shortening phase must be compromised at some point in order to produce more power and improve the jumping height.